Urbanización e industrialización en zonas periurbanas: el caso de una asociación de Carapongo (Lurigancho, Lima) - Cavani Guzmán, Pierina (2024)
This article aims to discuss one of the findings of the research conducted for my undergraduate thesis: the impact of urbanization and industrialization processes on peri-urban agricultural production in the Nuevo Horizonte de Carapongo association. In this regard, the goal is to analyze the development of industrialization and urbanization phenomena in this association and then examine their relationship with the changes generated in the agricultural production of the area. Based on the concepts of peri-urban space and deagrarianization, this research seeks to contribute to the academic discussion on the deagrarianization process of peri-urban spaces.